The understanding about Islamic Insurance among students diploma Part 4 of faculty ACIS in UiTM Puncak Alam / Nuramira Arifa Mohd Saharudin. - Mohd Saharudin, Nuramira Arifa (2019)
Malaysia’s Takaful Industry grew incredibly fast and became increasingly recognized year after year since the enactment of Takaful Act 1984 as a major contributor to Malaysia’s overall Islamic financial system. In addition, the establishment of Takaful is a new alterative way to promote and enhance the economic system. It is also an option to replace conventional insurance products which is prohibited in Islam. However, the participation and knowledge of Takaful are still low especially among the Muslims in Malaysia. Hence, the aim and objectives of this study were to analyze the level of knowledge about Islamic insurance among the students, evaluate students’ preferences towards takaful products in Malaysia and give some ideas to enhance and provide better improvement of Takaful institution in Malaysia. In this study, the researcher adopted the quantitative method which is survey. Next, the sample of this research was selected among 98 students Diploma Part 4 of Faculty Academy Contemporary Islamic Studies in UiTM Puncak Alam. The results show that the knowledge about takaful are low among the respondents but they still prefer takaful products instead of the conventional insurance.